The Influence of Pappasang Ri Kajang in Teaching Moral Values in Early Childhood: A Quasi-Experimental Study - Anriani, Ayu; Syamsuardi, Syamsuardi; Amri , Nuralim; Intisari, Intisari (Program Studi Magister Pendidikan Anak Usia Dini, 2025)
This research is based on the problem of low moral values in early childhood, where children have difficulty behaving politely, behaving honestly, and humbly. According to Weikart, through exploration and problem-solving is an active way for children to learn, which is considered important to help children become polite, honest, and humble in facing new situations with moral values. Therefore, this study aims to analyze the influence of Pappasang Ri Kajang on the ability of moral values in children aged 5-6 years. This study uses a quantitative approach with a quasi-experimental method with a post-test design of one group. The research subjects consisted of 15 children in Wulil Amri Mannuruki Kindergarten Group B who were selected from the research population using purposive sampling techniques. Data is collected through observational guidelines that measure three main aspects: recognizing problems, finding solutions, and evaluating outcomes. The results of the study showed a significant improvement that can be seen from the ability of children to behave politely, honestly, and simply after the implementation of Pappasang Ri Kajang . There was a difference in the average pre-test score of 26.62 increasing to 53.31 at the posttest with a significance value of 0.001 (p <0.05). The application of Pappasang Ri Kajang has been proven to be effective as an experiential learning method to improve early childhood moral values, so that it can be a relevant alternative for educators.